2011
DOI: 10.1186/1477-7525-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Japanese version of the Pediatric Quality of Life Inventory (PedsQL) Cancer Module

Abstract: BackgroundThe PedsQL 3.0 Cancer Module is a widely used instrument to measure pediatric cancer specific health-related quality of life (HRQOL) for children aged 2 to 18 years. We developed the Japanese version of the PedsQL Cancer Module and investigated its reliability and validity among Japanese children and their parents.MethodsParticipants were 212 children with cancer and 253 of their parents. Reliability was determined by internal consistency using Cronbach's coefficient alpha and test-retest reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 25 publications
(29 reference statements)
5
55
1
7
Order By: Relevance
“…In a study carried out in Libano 4 with 85 children aged between 7 and 18 years, a mean HRQoL of 80% (64%-91%) was found. A study with 212 Japanese families of children aged between 5 and 18 years found self-report scores of 78% (67%-93%) and proxy-report scores of 75% (62% and 85%) 5 . In China…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study carried out in Libano 4 with 85 children aged between 7 and 18 years, a mean HRQoL of 80% (64%-91%) was found. A study with 212 Japanese families of children aged between 5 and 18 years found self-report scores of 78% (67%-93%) and proxy-report scores of 75% (62% and 85%) 5 . In China…”
Section: Literature Reviewmentioning
confidence: 99%
“…23 Nevertheless, the QoL had statistically meaningful differences in the variants, age of the child diagnosis, 9,11 guardian age 9 , child and adolescent without treatment. ≤12 months and >12 months, [4][5][6]21, cancer diagnosis and epilepsy, 3 for nutrition condition, 18 death in less than six months and over six months after interview.…”
Section: Discussionmentioning
confidence: 96%
“…The small size of sample may limit the power of statistic analysis 2,16,18,19,22 might justify not find significant differences between different application times, 19 age, race, 15 sex, 5,8,9,15,16,24 and in with or without treatment 11 , and in home cares and standard treatment in reports of children. 23 Nevertheless, the QoL had statistically meaningful differences in the variants, age of the child diagnosis, 9,11 guardian age 9 , child and adolescent without treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, generic measures are suitable for QOL assessment, regardless of the child's specific condition, and can be used to compare patient groups with different diagnoses or a general population in order to determine the impact of a health condition or disease on HRQOL [2]. In Japan, several diseasespecific self-reported measures are available for diseases such as asthma [32], cancer [33], brain tumor [34] and behavioral problems [35]. In addition, some generic measures are available for young adults (e.g., SF-36 [36] ), but to date, very few well-validated measures are focused on children.…”
Section: Discussionmentioning
confidence: 99%